(untitled) (Archives of Mechanics - Test, 2001)
A model for the prediction of the viscoplastic behaviour of polycrystalline ice is presented. This model is based on the minimization of the dissipation energy under the principle of minimal heterogeneity. The grain is supposed to behave as a linear transversely isotropic medium depending on one anisotropy parameter. Anisotropic textures can be considered, but the present numerical results are for an isotropic texture. The model then predicts a linear isotropic behaviour involving an effective viscosity. The latter depends on the prescribed value for the strain-rate heterogeneity and on the grain anisotropy parameter. The present model is compared with a self consistent model built under the same assumptions for the grain behaviour. The deviation from the no-correlation condition is studied.